The Discourse-Historical Approach: The Comparison of The Statelessness Identity in Germany and Latvia - Yanuar Rahmadan (GLOBAL INSIGHT JOURNAL, 2023)
The statelessness is not a a new issue within European countries. Statelessness had made some highlights but finally gained significant attention after the collapse of the former Soviet Union, Czechoslovakia and Yugoslavia in the late 1980s. This study aims to see how the European Commission and the European Network on Statelessness talk about identity in the statelessness issue in Germany and Latvia. Through the qualitative research method, specifically employs the Discourse-Historical Approach (DHA) from Ruth Wodak, this study aims to reveal the language and the linguistics used in the ad-hoc query and statelessness index to further investigate the identity perspective of statelessness issue in Germany and Latvia. The main finding is that there are several distincting between Germany and Latvia to handle statelessness issue in their respective countries. While Germany has a problem to conduct statelessness determination procedure, Latvia has succeed  to created its own statelessness determination procedure although in the end has created categorisation bias. This finding appears in both Statelessness Index and in the Ad-hoc query.Keywords: statelessness, identity, Germany, Latvia, Discourse-Historical approach